MENINGKATKAN KINERJA DOSEN MELALUI PENILAIAN INTEGRITAS DAN MOTIVASI DOSEN - Tarman, Manah; Mariatun, Ika Lis; Septiana, Aldila; Arisinta, Octaviana (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of Lecturer Integrity and Motivation on Lecturer Performance in the classroom, from students perspective. The sample consists of 89 students of the economics education study program STKIP PGRI Bangkalan. Integrity and motivation are considered fundamental prerequisites that empirically influence the quality of effective teaching. This study uses a descriptive quantitative method. The data collection method uses a questionnaire. Data analysis will be carried out using Multiple Linear Regression, after going through a series of classical assumption tests. The results of the study revealed that there is a significant influence of lecturer integrity partially on lecturer performance; there is a significant influence of lecturer motivation partially on lecturer performance; there is a significant influence of lecturer integrity and motivation simultaneously on lecturer performance. It is expected to provide empirical evidence regarding the contribution of lecturer moral-ethics and encouragement to the effectiveness of the learning process, as well as being a basis for institutions in improving the lecturer evaluation and development system.